PERAMALAN PERUSAHAAN PERUSAHAAN TARGET TAKE OVER DENGAN PENDEKATAN TOBIN'S Q DAN ANALISIS DISKRIMINAN DI PASAR MODAL INDONESIA TAHUN 2005 - Hotman T Pohan (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2008)
This research is designed to examine Tobin'Q Model and Discrimirnant Anal;ysis for implelementating in take over process or aquisition. We want to get empirical evidence the application of the Tobin'Q Model and Discriminant Analysis models in take over process in Jakarta Stock Exchange during 2005. The result of this research are ROE has significant differenctiation at level 0,05 so this ratio to be paid attention, in level 0,01 D/E is significant, but PER is not significant. Discriminrant Model that resulted of the research is Z = -0,036 + 0,22 ROE, and the model could use as guidance for aquisition.